Caracterização socioambiental, econômica da extração de argila no município de São Miguel do Guamá-PA - SANTOS, Deivid Teixeira (2020)
In recent decades, with the heated civil construction sector in Brazil, the Para ceramic industry commitment to product quality to win the market and is emerging as a leading producer poles of the north of the country, in this context the municipality of San Miguel the Guama located in the northeastern portion of the state of Pará stands out as a major producer of goods' 'Social Minerals' use in the construction industry with emphasis on derivatives clay, become according to SEDEME (Secretary of State and Development economic, Mining and Energy) the 4th largest Production Brazil Mining (by volume) Below Only the iron production and Aggregate (Sand and Gravel) with the Metropolitan Region of Belém and the municipality of Castanhal as major consuming centers, although currently has been increasing exports to the south-southeast of the country. In 2009 the municipality of Sao Miguel do Guama contributes a production of approximately 34,200,000 (thirty-four million, two hundred thousand) pieces / month and generated approximately 2,800 (two thousand eight hundred) direct jobs and indirect, presenting itself as the largest red ceramic producers in the State of Pará. According SINDCER (Union of Industries ceramics Sao Miguel do Guama and Region) in 2015 even with the crisis managed to achieve the incredible average of 55.2 million pieces / month and generated approximately 3,680 (three thousand six hundred and eighty) direct and indirect jobs, and These clays in brownish gray coloring municipality marked by ferruginous concretions and plastic appearance. This clay material is tightly controlled over geologic time by the hydrodynamic action of the Rio Guama and Irituia. These deposits are all tied to the floodplain of the rivers mentioned above. The most potentially economic clays of the region are located in shallower levels in the extraction areas and farther from the river beds, but within the flood zone thereof, that fact is probably due to non-deposition of organic matter brought by the rivers more distant points of its floodplain. Clays of Sao Miguel do Guama, has stood out enough in the consumer market for its high technological power in the production of tiles and bricks. This technological feature satisfies properties such as the breakdown voltage of the bending, the lower water absorption, color after firing, less me ferruginous concretion and low organic matter content.